Pengaruh Ekuitas, Pembiayaan Dan Dana Pihak Ketiga Terhadap Pertumbuhan Laba Pada PT Bank Mega Syariah Periode 2010 2014 - Nurlela Intan Putrima; Lestari Wuryanti (Jurnal Riset Akuntansi dan Manajemen Malahayati, 2017)
This study aims to determine the effect of equity, financing and third-party funds (DPK)against profit growth at PT Bank Mega Syariah period 2010 -2014. The object of this research is PTBank Mega Syariah which is the first Islamic commercial bank from the conversion of a conventionalbank, PT Bank Umum Tugu. Data analysis techniques in this study is a quantitative analysis that isexpressed with numbers - the numbers and calculations using statistical methods that assisted withSPSS 17.0. The data analysis used in this study is the test for normality, classic assumption test,multiple regression analysis, and hypothesis testing.The results of this study with multiple linear regression analysis showed that partial variable-significance 0.913 meaning Financing partially no significant effect on earnings growth, variable (X3)Funds partially significant effect on earnings growth, regression calculation results together- thesame (F test) indicates that the variable (X1) Equity, (X2) financing, and (X3) Third Party Funds(X2) Financing and (X3) Third Party Funds together - equally significant effect on earningsgrowth at PT Bank Mega Syariah.